Unraveling age-dependent potassium accumulation mechanisms and usage efficiency in two cupuaçu progenies in agroforestry systems - Silva, Diocléa Almeida Seabra; Viégas, Ismael de Jesus Matos; de Souza, Luma Castro; Costa, Milton Garcia [UNESP]; de Oliveira Neto, Cândido Ferreira; Okumura, Ricardo Shigueru (Springer Nature, 2025)
To fully realize the production potential and maintain the prominence of cupuaçu in the market, a comprehensive understanding of its mineral nutrition, especially potassium (K) absorption in agroforestry systems is necessary. Therefore, this study aimed to elucidate the dynamics of K accumulation and its usage efficiency throughout the life cycle in two cupuaçu progenies in agroforestry systems. An experimental design employing a 2 × 4 factorial scheme was utilized involving two distinct progenies (PMI 186—Codajás and PMI 215—Manacapuru) and four cultivation ages, with five repetitions. Statistical analyses encompassed regressions and analyses of variance to comprehend the K accumulation in progenies 186 and 215, as well as in their different plant components [leaves (L), stems (S), primary branches (PB), and secondary branches (SB)]. In the leaves of progeny 186, K decreased from 7.34 to 6.55 g kg−1, while in progeny 215, it dropped from 6.56 to 4.80 g kg−1. The stem of progeny 186 showed a reduction from 7.01 to 5.06 g kg−1, and in progeny 215, a reduction from 6.96 to 4.25 g kg−1. Notably, progeny 215 exhibited a consistent trend of accumulating more K than progeny 186 throughout the study period. These findings underscore the fundamental role of K in cupuaçu tree nutrition and reveal distinct patterns of K accumulation among the studied progenies. Such information provides valuable guidance for optimizing the production of this unique fruit tree in agroforestry systems in the Amazon.
Keywords: Amazon; Fruit tree; K dynamics; K use efficiency; Nutritional efficiency; Theobroma grandiflorum(Willd. ex Spreng.) Schum